Aprendizagem docente: o conhecimento compartilhado sobre inclusão e a formação continuada no ensino fundamental - Wisch, Tásia Fernanda (2013)
This research is part of the Research Line Training, Knowledge and Professional Development Program for Postgraduate Education, Federal University of Santa Maria / RS. The study focuses on understanding how shared reflective practice contributes to the learning of teaching in basic education in an inclusive setting. The main theoretical reflections that contribute to this research in the context of inclusion are: Mantoan (2008), Freitas (2008), Fonseca (2003), Freire (2005, 2009), Martins (2010), Rodrigues (2008), Dutra (2008) and Bayer (2006). Speaking about the concept of activity we come from studies considering Vygotski (1994, 1995, 2009), Leontiev (1984, 1978, 1998) Davidov and Markova (1987), Rossetto (2013). Regarding the training of teachers we take into consideration of Bolzan (2002, 2007, 2009, 2010), Ferry (2004), Marcello Garcia (1999) Michels (2009), Nóvoa (1992, 1997) and Imbernon (2005, 2006, 2010). To discuss about the reflection and action, we highlight Zeichner (1993) and Shön (1997). The research takes part from a training event geared for inclusive processes in which teachers of a public school in Ijuí / RS proposed to discuss inclusion. The methodology used is the qualitative approach of narrative sociocultural nature, which has semi-structured interview as an instrument of data collection. In order to illustrate the research context, we also used daily meetings which were written by the researcher. From the recurrence narratives of the collaborators and the diaries it was possible to emphasize one category that we called Learning Teaching. This category is guided by the desire of learning, seeking new learning and learning from another person. Thus, this category is formed by categorical dimensions: Conceptions of Inclusion, Collaborative work and Spaces / places of training, these dimensions, which are interwoven together and consolidate the process of learning to teaching in a context of inclusion.